UCI Critical Theory and Contemporary Art Practice: Jacques Derrida, Jean-François Lyotard, Bruce Nauman, and Others With a Prologue by Georges Van Den Abbeele - Nycz, Ryszard; Nycz, Ryszard; Bobrowska, Ewa (Peter Lang, 2020)
This book is unique in both its subject matter and its approach. It focuses on the collaboration of J. Derrida, J.-F. Lyotard, J. Hillis Miller, D. Carroll, F. Jameson and others at the Critical Theory Institute at the University of California, Irvine and on the application of critical theory for the analysis of contemporary American visual art. The critical and philosophical analysis concerns the art of Bruce Nauman, Kosuth, Burden, Christo, Wodiczko, Johns, Rauschenberg, and others. The focus of the book is on irony and the sublime. The book also includes the original Prologue by G. van Den Abbeele (Dean of the School of Humanities at UC Irvine 2013-2018) on the history of Critical Theory in the United States, and at UCI, in particular. The CTI's uniqueness consisted in it being one of the best centers of the Critical Theory studies in the United States.